PENGARUH PERCEIVED PARENTAL REWARD, ENTREPRENEURIAL SELF EFFICACY, YANG DIMODERASI FAMILY BUSINESS INVOLVEMENT TERHADAP ENTREPRENEURIAL INTENTION DI UNIVERSITAS PELITA HARAPAN - Zoel Hutabarat; Denny Larson; Marchel Denny Irawan (IDEI: Jurnal Ekonomi & Bisnis, 2021)
The number of business people who started from a family business in Indonesia were quite large. But the number of companies that prepare successors to continue and develop the family business could be counted on fingers. This study aimed to determined the effect of Perceived Parental Reward, Entrepreneurial Self Efficacy, which was moderated by Family Business Involvement on Entrepreneurial Intention. This study used quantitative research by distribute 200 questionnaires and tested using PLS Structural Equation Modeling (SEM) to evaluate the reliability and validity of measurement models and structural models. The results showed that there was a positive influence between the Perceived Parental Reward, Entrepreneurial Self Efficacy, which was moderated by Family Business Involvement on Entrepreneurial Intention. From these results it was hoped that the campus could form a supportive environment for the development of family businesses. It did not always form the mindset to form a new business so that a growing family business was not abandoned or no longer want to build a family business. Jumlah pelaku bisnis yang memulai dari bisnis keluarga di Indonesia cukup banyak. Namun jumlah perusahaan yang menyiapkan penerus untuk melanjutkan dan mengembangkan bisnis keluarga bisa dihitung dengan jari. Penelitian ini bertujuan untuk mengetahui pengaruh Perceived Parental Reward, Entrepreneurial Self-Efficacy yang dimoderatori oleh Family Business Involvement terhadap Entrepreneurial Intention. Penelitian ini menggunakan penelitian kuantitatif dengan menyebarkan 200 pertanyaan dan diuji menggunakan PLS Structural Equation Modeling (SEM) untuk mengevaluasi reliabilitas dan validitas model pengukuran dan model struktural. Hasil penelitian menunjukkan bahwa terdapat pengaruh positif antara Perceived Parental Reward, Entrepreneurial Self-Efficacy yang dimoderatori oleh Family Business Involvement terhadap Entrepreneurial Intention. Dari hasil tersebut diharapkan kampus dapat membentuk lingkungan yang mendukung bagi pengembangan usaha keluarga. Tidak selalu membentuk pola pikir untuk membentuk usaha baru agar usaha keluarga yang sedang berkembang tidak terbengkalai atau tidak mau lagi membangun usaha keluarga.